Multiple Dorsal Hand Actinic Keratoses and Squamous Cell Carcinomas: A Unique Presentation following Extensive UV Nail Lamp Use - Madison C. Ratycz; Joyce A. Lender; Lorie D. Gottwald (Karger Publishers, 2019)
Squamous cell carcinoma (SCC) is the second most common skin cancer worldwide, and exposure to ultraviolet (UV) light is a major cause of SCC. UV nail lamps can be used for drying and hardening acrylic or gel nail polish. We report a case of a 52-year-old Caucasian woman with an 18-year history of UV nail lamp use every 3 weeks and an 18-year history of weekly tanning bed use who presented with over 25 actinic keratoses and two SCC in situ on her dorsal hands. Of note, this patient has never had any previous biopsies, skin cancer or precancers, or skin cancer or precancer treatment at any time in the past and on skin examination had no precancers or cancers elsewhere on her body. We also review the existing research regarding nail lamp use, which overall suggests that the risk of carcinogenesis is low, and discuss ways dermatologists can educate patients regarding proper UV nail lamp use to minimize risks. This patient's extensive UV nail lamp use coupled with UVA exposure from tanning beds may have put her at particular risk and exacerbated the effects of the nail lamp alone.